The concise Oxford dictionary of politics - McLean, Iain (Oxford University Press, 2003)
Written by a team of leading political scientists, the Oxford Dictionary of Politics contains more than 1,700 entries, including new material on topics such as NGOs, butterfly ballots, decentralisation, ethnic cleansing, and direct action. Covering political thinkers, institutions, and concepts, the dictionary has an international perspective. Appendices list the political leaders of a range of countries and international institutions. Fully updated and revised, this best-selling dictionary of political terms will prove invaluable to students and academics studying politics and related disciplines, as well as professionals and the general reader